Genome-wide association and transcriptome studies reveal the segregation mechanism of mantle markings in three-way cross hybrid abalone - Xiao, Qizhen; Gong, Shihai; Shen, Yawei; Lu, Yisha; Lai, Xinlian; Peng, Wenzhu; Huang, Zekun; Han, Zhaofang; Ji, Hongjing; Gan, Yang; Luo, Xuan; You, Weiwei; et al. (Frontiers in Marine Science, 2022)
Trait separation which often appears in shellﬁsh progeny, has been commercially used in shellﬁsh breeding projects. A three-way cross hybrid abalone was produced with heterosis in growth performance and thermal tolerance, and with segregation in mantle marking. However, the inheritance mechanism of mantle marking is unclear. In this study, mantle marking was demonstrated to be a qualitative trait, following simple Mendelian inheritance, through inheritance pattern analysis of the presence of black markings on the mantle in five families of three-way cross of hybrid abalone. Thermal tolerance of abalone was assessed by the Arrhenius breakpoint temperature (ABT) of cardiac performance and a correlation between mantle marking and thermal tolerance of abalone was verified. A genome-wide association study (GWAS) for mantle marking was conducted using 603,067 high-quality single nucleotide polymorphisms (SNPs) derived from 57 individuals with mantle markings (Y group) and 58 individuals without mantle markings (N group). A total of 493 SNPs that were significantly (p < 2.32E–07) associated with mantle markings were mainly distributed on chromosome 15. In the potential signiﬁcantly associated region, 80 genes, including pigmentation-related genes PTPRT, PTPRC, PNCA, and CALM4 were annotated. Transcriptome analysis of the two groups showed that the expression levels of these genes (PTPRT, DDT-b, ATOX1, SLC6A3, and GSTO1) were significantly different, and they may play important roles in the formation of mantle markings in the three-way cross hybrid abalone. Overall, our data provide valuable information for deciphering the phenotype diﬀerences of mantle marking in three-way cross hybrid abalone and help in the molecular marker-assisted breeding in abalone.